PENGARUH MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI TERHADAP SKILLS ABAD 21 PADA ANAK USIA DINI - Ratu Yustika Rini; Dinu Rijkiyah; Siti Nur Yuliyanti; Ela Oktapiani (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to determine and describe whether there is an effect of animated video-based learning media on 21st century skills in early childhood. This study uses the Pre-Experimental Design research method in which this design uses a pretest-posttest control group design. The samples in this study were students in group B 1, totaling 26 students (control class) and B 2 with 26 students (experimental class). Data collection techniques were carried out using open-ended questions guided by the teacher. The tests are in the form of pretest and posttest. The initial stage is given a pretest in each class, then learning is carried out using animated videos in the experimental class, in the control class using ordinary learning. Then given a posttest to determine the final ability of students. Based on the results of the normality test, each experimental class and control class obtained a value of sig> 0.05, so that the data were normally distributed. The results of hypothesis testing with t test obtained a significant value of 0.000, sig value of 0.000